Pina Bausch's Dance Theater: Company, Artistic Practices and Reception - Klein, Gabriele (transcript, 2020)
This volume provides new, ground-breaking perspectives on the globally renowned work of the Tanztheater Wuppertal and its iconic founder and artistic director, Pina Bausch. The company's performances, how it developed its productions, the global transfer of its choreographic material and the reactions of audiences and critics are explained as complex, interdependent and reciprocal processes of translation. This is the first book to focus on the artistic research conducted for the Tanztheater's international coproductions and features extensive interviews with dancers, collaborators and spectators and provides first-hand ethnographic insights into the work process. By introducing the praxeology of translation as a key methodological concept for dance research, Gabriele Klein argues that Pina Bausch's lasting legacy is defined by an entanglement of temporalities that challenges the notion of contemporaneity.